2017
DOI: 10.21873/anticanres.11793
|View full text |Cite
|
Sign up to set email alerts
|

Nicotine Exposure Augments Renal Toxicity of 5-azacytidine Through p66shc: Prevention by Resveratrol

Abstract: Abstract. Background Studies demonstrated that nephrotoxicity is a frequent side-effect of various anticancer agents that hampers their clinical use (1). Previously we reported that the anticancer agent 5-aza-cytidine (AZA) elicits oxidative stress-mediated toxicity in cultured renal proximal tubule cells via transcriptional upregulation of the prooxidant p66shc gene and consequent increase in mitochondrial reactive oxygen species (ROS) release (2). Studies revealed that smoking augments severity and progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 18 publications
(25 reference statements)
0
3
0
Order By: Relevance
“…Whereas previous reports have indicated links of nicotine exposure to increased renal damage via p66Shc-mediated oxidative stress (1,45), this study demonstrated further increased damage induced to the renal tubules due to the combination of 5AZA and nicotine. These data suggest both a mechanism to a phenomenon that has been plaguing physicians trying to treat cancer patients (39,83) and also proposes that the antioxidant resveratrol could be used a therapeutic treatment to decrease the p66Shc-induced oxidative stress induced both by the anti-cancer treatment as well as nicotine exposure (6).…”
Section: P66shc and Renal Toxicity Of Anticancer Agentsmentioning
confidence: 88%
See 1 more Smart Citation
“…Whereas previous reports have indicated links of nicotine exposure to increased renal damage via p66Shc-mediated oxidative stress (1,45), this study demonstrated further increased damage induced to the renal tubules due to the combination of 5AZA and nicotine. These data suggest both a mechanism to a phenomenon that has been plaguing physicians trying to treat cancer patients (39,83) and also proposes that the antioxidant resveratrol could be used a therapeutic treatment to decrease the p66Shc-induced oxidative stress induced both by the anti-cancer treatment as well as nicotine exposure (6).…”
Section: P66shc and Renal Toxicity Of Anticancer Agentsmentioning
confidence: 88%
“…It has been observed that the epigenetic modifying anticancer drugs trichostatin A (TSA) and 5-aza-cytidine (5AZA) induce renal tubular injury in part by increasing mitochondrial ROS production (69) and that this ROS corresponds to increased expression and mitochondrial localization of p66Shc (2,107). Interestingly, in a recent study by Arany et al (6), it was observed that nicotine exposure augments the renal toxic effects of 5AZA. Whereas previous reports have indicated links of nicotine exposure to increased renal damage via p66Shc-mediated oxidative stress (1,45), this study demonstrated further increased damage induced to the renal tubules due to the combination of 5AZA and nicotine.…”
Section: P66shc and Renal Toxicity Of Anticancer Agentsmentioning
confidence: 99%
“…This mostly transpires as the Ser36 phosphorylated p66shc does not translocate to the mitochondria, which indicates its pro-oxidant function; however, it activates the ARE, and, consequently, a set of antioxidant genes that harbor the ARE in their promoter. RSV activates the ARE via Nrf2, which induces the HO-1 promoter and, hence, offers protection to the cell via the cytoplasmic p66shc/Nrf2/HO-1 axis [ 197 ].…”
Section: Resveratrol: Emerging As a Potential Antioxidant Nutraceuticalmentioning
confidence: 99%